Recovery of wastes by pyrolysis: effect of experimental conditions - Paradela, Filipe (2009)
This work aimed to study the recovery of three types of waste by the process of pyrolysis: biomass, plastics and used tyres. The effects of experimental conditions in products yield and composition were studied. The increase of reaction time increased alkane content both in gas phase from 53% to 70% v/v and in liquid fraction from 48% to 60% w/w. The rise of reaction temperature led to a decrease of liquid yield (from 82% to 73% w/w), which was followed by the increase of solids and gases. The increase of reaction temperature also allowed the increase of the alkane content in gas phase from 39% to 70% v/v. The increase of initial pressure did not lead to appreciable variations in product yields or composition. The parameter that most affected products yield and composition was plastics content on the wastes initial mixture. The enhancement of this parameter increased liquids yield from 33% to 92% w/w, at the expenses of solids and gases contents and also decreased aromatics contents from 52% to 28% w/w.